2005
DOI: 10.1213/01.ane.0000180198.13467.df
|View full text |Cite
|
Sign up to set email alerts
|

Doxapram Only Slightly Reduces the Shivering Threshold in Healthy Volunteers

Abstract: We determined the effects of doxapram on the major autonomic thermoregulatory responses in humans. Nine healthy volunteers were studied on two days: Control and Doxapram (intravenous infusion to a plasma concentration of 2.4 ±0.8 μg/mL, 2.5 ±0.9 μg/mL, and 2.6 ±1.1 μg/mL at the sweating, vasoconstriction, and shivering thresholds, respectively). Each day, skin and core temperatures were increased to provoke sweating, then reduced to elicit peripheral vasoconstriction and shivering. We determined the sweating, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
(23 reference statements)
0
11
0
1
Order By: Relevance
“…Therefore, both doxapram and demerol were effective in the treatment of postoperative shivering, with demerol being perhaps slightly better. However, a more recent study has shown that doxapram's effect on shivering threshold is minor, lowering the shivering threshold in normal volunteers by only 0.5°C (28).…”
Section: Prevention Of Shiveringmentioning
confidence: 95%
“…Therefore, both doxapram and demerol were effective in the treatment of postoperative shivering, with demerol being perhaps slightly better. However, a more recent study has shown that doxapram's effect on shivering threshold is minor, lowering the shivering threshold in normal volunteers by only 0.5°C (28).…”
Section: Prevention Of Shiveringmentioning
confidence: 95%
“…Ineffective drugs include ondansetron (a 5HT-3 antagonist used for prevention and treatment of nausea and vomiting), (70) magnesium sulfate, (71) and doxapram (effectively, a central dopamine agonist) (72). Dantrolene is a peripherally acting skeletal muscle relaxant primary used for treatment of malignant hyperthermia crises.…”
Section: Nonopioidsmentioning
confidence: 99%
“…Numerous pharmacological agents 7,10,[16][17][18][19][20][21][22][23][24][25] (Table 2) that reduce the vasoconstriction and shivering thresholds have been used to manage shivering during therapeutic hypothermia. According to the ILCOR, 3 sedative and hypnotic agents are often used to decrease metabolic demand and facilitate mechanical ventilation in comatose patients who lack signs of awakening within the first 5 to 10 minutes after return of spontaneous circulation.…”
Section: Pharmacological Methodsmentioning
confidence: 99%